DIAGNOSIS OF THE AERODYNAMIC SURFACE OF AIRCRAFT - Казак, В. М.; Гальченко, С. М. (Proceedings of National Aviation University (archive), 2021)
The possibility of organizing the diagnosis of the outer surface of aircraft in flight is considered. A method for determining the moment and place of sudden damage to the surface of the aircraft is proposed.